Privación del sueño y reserva cognitiva en adultos mayores de la ciudadela San Marino en la ciudad de Vinces - Altamirano Gaibor, Mayra Tatiana (2024)
Sleep deprivation, both in its chronic and acute forms, represents a condition that can have significant repercussions on the performance of both motor and cognitive activities. It is crucial to recognize the importance of preserving and caring for this vital process to guarantee adequate physical and mental functioning. On the other hand, cognitive reserve refers to the intrinsic capacity of the brain to resist the changes associated with physiological aging, largely preserving the integrity of cognitive functions. The purpose of this study is to examine in detail the effects that sleep deprivation can have on the cognitive reserve of older adults in the city of Vinces, specifically in the San Marino citadel community. To carry out this analysis, a descriptive methodology and a non-experimental design have been implemented, with a quantitative approach and an analytical method. The study sample was composed of 40 older adults selected from an initial population of 100 individuals, using a survey as a data collection technique and the Cognitive Reserve Questionnaire (CRC) as an evaluation instrument. The bibliographic review carried out focused on the relevant variables for a deep understanding of the problem in question. Ultimately, this study aims to contribute to existing knowledge about the relationship between sleep deprivation and cognitive reserve in older adults, with the hope of providing valuable information that can be used to improve the quality of life and well-being of this important population.